What is driving complaints during the pandemic?. (2nd April 2021) - Mackenzie, Peter; Simsek, Ceylan
Abstract : Dr Emma Davies, Medicolegal Consultant at Medical Protection, looks at how Covid-19 has impacted on patient complaints and some of the common themes that are emerging